A critical investigation into the process of negotiating a mathematics education curriculum with pre-service teachers - Westaway, Lise (Rhodes University, Faculty of Education, Department of Education, 2005)
It's almost like a dinner party and a buffet. A dinner party you get dished up stuff and you eat it and a buffet you can choose what you want out of a range of stuff. I mean think about it when you go to a dinner party- they always dish up something you don't like and you don't want to eat it anyway. It's the same if you have a lecturer in the front that just dishes out what you're going to learn, ... you have to learn it. But in terms of the curriculum negotiation process, I've got to choose what I wanted to leam. (Melissa II 27/11/01: 3) This thesis focuses on the process of negotiating the curriculum with twelve pre-service teachers registered for the Bachelor of Education (Primary) Degree during their Mathematics Education Course in their third year of study. The research is presented methodologically as an action research located within two paradigmatic positions, interpretive and critical. The research attempted to understand, interpret and critique the process of curriculum negotiation within the context of teacher education in South Africa In order to understand the negotiated curriculum process, experiences of the participants are presented through the use of their voices within the thesis. The interpretation is based on the construction and reconstruction of meaning during the enactment of the negotiated curriculum process and during the writing and reviewing of this thesis. The critique is rooted in the historical, cultural and social contexts of both the students and the author. The main contention of this thesis is that curriculum negotiation is not necessarily a suitable vehicle for developing a critical pedagogy in pre-service teacher education when all the participants form a homogenous group in this case, white middle-class women. The democratic values promoted within the context of our curriculum negotiation were fraught with dilemmas and entrenched the values of western liberalism. At most, the curriculum negotiation process and the development of a democratic learning environment, promoted a conscientisation at an individual level, namely a ' transformation of consciousness' . The democratic values promoted in our pedagogy were not sufficient in bringing about social change, a 'transformation for social action'.
Keywords: Teacher participation in curriculum planning -- South Africa; Curriculum planning -- South Africa; Curriculum change -- South Africa; Mathematics -- Study and teaching -- South Africa; Teachers -- Training of -- South Africa; Mathematics teachers -- Training of -- South Africa